The Paradox of Faith: White Administrators and Antiracism Advocacy in Christian Higher Education. Issue 4 (8th August 2017) - Ash, Allison N.; Clark, Karen; Jun, Alexander
ABSTRACT: The purpose of this qualitative study was to explore the experiences of White administrators in Christian higher education within the United States who were active in antiracism advocacy. A team of researchers employed narrative inquiry borrowing from grounded theory approaches and interviewed eight administrators from four member institutions of the Council for Christian Colleges & Universities (CCCU) in the Midwest region of the United States. Data analysis indicated that the participants' faith both hindered and helped in their antiracism advocacy. The process of politicizing racial justice issues and participants experiencing a fear of suspicion from institutional leaders because of their antiracism advocacy were identified as being hindrances to their antiracism efforts. However, the administrators cited their interpretations of Christian scriptures and their personal faith commitments as motivators for their antiracism work. Implications for practice include the encouragement of higher education communities to make systemic (rather than individual) changes, and to approach racial justice first and foremost from a biblical and theological perspective.